The Reality of Using Blended Learning in the Arab East Colleges from the Point of View of Faculty Members - Theqah, Mahasin Hussain; Al-Manhrawi, Dalia Nabil (Journal of Curriculum and Teaching Methodology, 2024)
This study aimed to identify the reality of using blended learning in Arab East colleges from the faculty members' point of view, to identify the difficulties that impede the use of blended learning in Arab East colleges from the faculty members' point of view, and to provide developmental proposals for using blended learning in Arab East colleges from the faculty members' point of view. In order to achieve these objectives, the researcher used the descriptive method and relied on the questionnaire as a tool to gather the required information for this study. The questionnaire was applied to 65 members of the Arab East colleges in Riyadh city, the number of respondents to the study was 62. The study reached a set of findings, most notably: The study sample's individuals consider that blended learning is used largely in Arab East colleges from the faculty members' point of view. with an arithmetic aaverage of (4.08), The results also showed that the study sample's individuals believe that there are moderate difficulties impeding the use of blended learning in Arab East colleges from the faculty members' point of view with an arithmetic average of (3,30). The most significant of these difficulties were the large amount of administrative work assigned to the faculty members with an arithmetic of (4,16). The results also presented the main suggestions, which was providing the infrastructure for blended learning environment in the college and providing faculty members with information on the technical requirements (hardware and programs) needed to succeed in the blended course prior to its inception.
Keywords: E-learning; Blended learning